Numerical simulation of radial and axial compressed elastomeric O-ring relaxation (Global Journals of Research in Engineering, 2012)
The elastomeric O-ring gaskets are often used in pressurized hydraulic and pneumatic equipments to ensure their sealing. The quality of the O-ring is measured by achieving the desired tightness level. The satisfaction level of practical operation depends on the consistency of long-terms mechanical properties located during the useful life and on the conditions of assembly installation and the O-ring location. Indeed, the gasket is pressed on flat faces or housed in specially arranged grooves for which the dimensions influence greatly the assembly behavior. In this article, an axisymmetric finite element model is proposed to simulate the O-ring relaxation behaviour during the few first days of its installation in both the unrestrained and restrained radial and axial loading cases. The contact stress profiles and the peak contact stresses are determined versus the time relaxation in order to specify the working conditions thresholds.
Keywords: O-ring; contact pressure; relaxation; FEA; Radial and axial loading